A development machine for measuring the precision and the response time of punches - Jaysrichai, T.; Srikongphan, K.; Jurarakpong, P. (The Open Biomedical Engineering Journal, 2019)
Robo-Boxing Trainer machine consisted of four targets. Each punching target has eight sensors and eight LED lights. Operating software, which programmed by PLC-CX programmer and DOPSoft (delta), can set the punching series and alarm signals. It recorded the response time from the starting signal to making contact with the target, calculating precision in percentage. This software could be set and recorded maximal 40 series and maximal 100 punches in each punching series. Researchers compared the accuracy of counting time with Digital Oscilloscope and tested the efficiency of sensors` cutting signal. This study found the counting time to be of high accuracy (100% and 98.8%). The cutting sensors' signal test found to be efficient. Conclusion